2022
DOI: 10.32768/abc.202292174-178
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Mammographic Screening of Breast Cancer in Women: a Cross-sectional Study in Southeastern Iran

Abstract: Background: Breast cancer is one of the most prevalent cancers in women in Iran and many other countries around the world. This cancer is the most critical cause of malignancy-related mortality in women. Early detection of breast cancer through mammographic screening of breast cancer greatly increases the chance of a successful treatment. This study aimed to explore the obstacles to mammographic screening of breast cancer in women.Methods: This cross-sectional study was carried out among 812 women over the age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…These findings are consistent with those of previous studies that identified fear and anxiety as significant barriers to MS uptake. 34,35 A systematic review by Wardle et al found that women's fear of BC and discomfort associated with the screening procedure were crucial factors in their decision not to participate in MS programs. 32 In addition to radiation concerns and pain during the examination, the present study participants reported concerns about pain during the examination.…”
mentioning
confidence: 99%
“…These findings are consistent with those of previous studies that identified fear and anxiety as significant barriers to MS uptake. 34,35 A systematic review by Wardle et al found that women's fear of BC and discomfort associated with the screening procedure were crucial factors in their decision not to participate in MS programs. 32 In addition to radiation concerns and pain during the examination, the present study participants reported concerns about pain during the examination.…”
mentioning
confidence: 99%